Enhancing higher education: Integrating micro-credentials and digital badges into university curricula in Ukraine - Valentyna Bobrytska; Tetiana Reva; Hanna Krasylnikova; Svitlana Protska; Sergiy Krasylnikov; Iryna But (Ricerche di Pedagogia e Didattica, 2025)
This study investigates the impact of integrating digital badges and micro-credentials into university curricula on student engagement, motivation, and employability. Using a mixed-methods approach, both quantitative data (Wilcoxon signed-rank tests for pre- and post-intervention assessments) and qualitative data (focus groups with students, course trainers, and employers) were analyzed. Findings reveal that micro-credentials significantly enhanced student engagement and motivation, as well as improved perceived employability. Course trainers noted the effectiveness of digital badges in providing structured feedback and fostering goal-oriented learning. Employers valued the skills demonstrated by micro-credentials but recommended incorporating emerging industry skills and soft skills for greater relevance. Challenges related to system navigation and technical integration highlight the need for clearer guidance and technological support. Further research is needed to explore the long-term impact of micro-credentials on career advancement and to assess their broader applicability across various sectors.